2011
DOI: 10.1097/rhu.0b013e31820e7e8d
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Systemic Sclerosis in a Healthcare Plan in Buenos Aires

Abstract: Despite potential biases, these data are in agreement with others from different parts of the world and the first obtained in Argentina and, to our knowledge, in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 24 publications
0
6
0
4
Order By: Relevance
“…SSc is rare but can have poor prognosis and low survival rate. Its prevalence is 56.3–341 cases per million population [3, 4], but the incidence and prevalence of SSc have increased, particularly in the USA and Australia [5].…”
Section: Introductionmentioning
confidence: 99%
“…SSc is rare but can have poor prognosis and low survival rate. Its prevalence is 56.3–341 cases per million population [3, 4], but the incidence and prevalence of SSc have increased, particularly in the USA and Australia [5].…”
Section: Introductionmentioning
confidence: 99%
“…11 Another study carried out in Buenos Aires showed data very similar to ours, since they found a global prevalence of 29.6 per 100,000 inhabitants, with a prevalence in the female population of 47.7 per 100,000 inhabitants, and 2.8 per 100,000 inhabitants in the male population, as well as an average age at diagnosis of 66 years. 12 Another study that yielded similar results is the one conducted in Lugo, Spain, with a global prevalence of 27.7 per 100,000 inhabitants, 77% females. 13 A review made in Australia by Morrisroe et al 14 showed a prevalence of 23.3-86 per 100,000 inhabitants, with female predominance, with a maximum female:male ratio of 5:1.…”
Section: Discussionmentioning
confidence: 74%
“…Rosa et al utilized a retrospective analysis of electronic medical records from a hospital in Argentina to estimate the 2004 point prevalence and the incidence density of SSc from 1999 to 2004 . The estimated point prevalence of SSc in Argentina was 29.6 cases per 100 000 persons, following a broad case definition criterion, namely, a combination of ACR 1980 and/or Le Roy and Medsger 2001 criteria . The estimated incidence density was 2.12 cases per 100 000 person‐years …”
Section: Resultsmentioning
confidence: 99%
“…The estimated point prevalence of SSc in Argentina was 29.6 cases per 100 000 persons, following a broad case definition criterion, namely, a combination of ACR 1980 and/or Le Roy and Medsger 2001 criteria . The estimated incidence density was 2.12 cases per 100 000 person‐years …”
Section: Resultsmentioning
confidence: 99%